EcoJustice, Citizen Science and Youth Activism Situated Tensions for Science Education - Mueller, Michael P.; Tippins, Deborah J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume draws on the ecojustice, citizen science and youth activism literature base in science education and applies the ideas to situated tensions as they are either analyzed theoretically or praxiologically within science education pedagogy. It uses ecojustice to evaluate the holistic connections between cultural and natural systems, environmentalism, sustainability and Earth-friendly marketing trends, and introduces citizen science and youth activism as two of the pedagogical ways ecojustice philosophy can be enacted. It also comprises evidence-based practice with international service, community embedded curriculum, teacher preparation, citizen monitoring and community activism, student-scientist partnerships, socioscientific issues, and new avenues for educational research.
Put Away Your Pencils-Reconceptualizing School Accountability through EcoJustice -- Provoking EcoJustice-Taking Citizen Science and Youth Activism Beyond the School Curriculum -- The Sustainable Farm School-Waldorf Philosophy and EcoJustice Theory in Aesthetic Contexts -- Building Teacher Leaders and Sustaining Local Communities through a Collaborative Farm to School Education Project-What EcoJustice Work Can PreService Teachers Do? -- Drawing on Place and Culture for Climate Change Education in Native Communities -- The Will of the Ancestors: A Collaborative Elementary Science Curriculum Design Initiative -- Eco, Social, or Any Other Justice? Critical Awareness among International Service-Learning Program Participants in Costa Rica -- Art to Capture Learning about the Longleaf Pine Ecosystem-Why a Picture is Worth a Thousand Words -- Ponder This? Editorial by J Myron Atkin -- The Commonplaces of Schooling and Citizen Science-Editorial by Xavier Fazio and Doug Karrow -- Living History-Challenging Citizen Science and Youth Activism through Historical Re-enacting -- Teaching with Citizen Science-It$1 (Bs More than Just Putting Out Fires! -- Carrizo Springs, Texas-The Story of the Systems Academy for Young Scientists (SAYS) -- Mediated Pedagogy in a Blended Environment: Impact of Processes and Settings -- Why the Secret of the Great Smoky Mountains Institute at Tremont Should Influence Science Education-Connecting People and Nature -- Democratic Participation with Scientists through Socioscientific Inquiry -- Ponder This? Editorial -- Youth Activism-Editorial -- Balancing Economic Utility with Civic Responsibility -- Pursuing Youth-led Socioscientific Activism: Conversations of Participation, Pedagogy, and Power -- Harnessing Youth Activism with/in Undergraduate Education: A Case Study of Change Lab -- Science and Democracy in Youth Environmental Action-Learning (3z(BGood(3y (BThinking -- Hitting the Big Screen-Urban Youth Activism through Documentary Film -- From Citizen Diplomacy to Youth Activism: The Story of the Global Thinking Project -- Seeing the Forest for the Trees! Conservation and Activism through Socioscientific Issues for Young Children -- Ponder This? Editorial by Angela Calabrese Barton.s
Keywords: Education; Science education; Teaching; Education -- Philosophy; Environmental law; Environmental policy; Education; Science Education; Environmental Law/Policy/Ecojustice.; Educational Philosophy; Teaching and Teacher Education; Electronic books